Influenza virus-specific cytotoxic T lymphocytes recognize HLA-molecules. Blocking by monoclonal anti-HLA antibodies. - Mcmichael, A; Parham, P; Brodsky, F; Pilch, JR (1980)
The effect of monoclonal anti-HLA antibodies on lysis of influenza virus-infected target cells by sensitized cytotoxic T lymphocytes was measured. Lysis was blocked, provided the antibody was present in a concentration sufficient to saturate the HLA determinants on the target cells. Antibodies to monomorphic HLA determinants and to beta 2-microglobulin inhibited. Antibody to HLA A2 and B17 blocked lysis of target cells that shared these antigens with the effector cell. It was concluded that the restriction elements for influenza virus-specific cytotoxic T cells are the HLA molecules themselves.